Teachers' Strategies in Teaching Speaking in Post-Pandemic - Hanum Noermalita; Neni Nurkhamidah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2023)
To develop students' speaking skills in English class, teachers require a variety of strategies based on needs, purpose, and situation. Therefore, this study aims to examine the types of teaching strategies are applied by teacher in teaching speaking after the Covid-19 pandemic at SMPN 264 Jakarta as well they way teachers implement them. Data was collected by applying observation and interview with three English teachers. The method implemented in this research is qualitative with a case study approach, data analysis was conducted in three stages: data reduction, data display, and conclusion drawing. The result of this study reveals that there are five strategies implemented by teachers in teaching speaking skills after the Covid-19 pandemic, they are: discussion, role-play, picture describing, storytelling, and drill. It is also shown that the teachers implement those strategy in various ways and learning topics. The results of this study are expected to be the basis for subsequent research on teacher teaching strategies in teaching speaking